Examining Human Resources Management Issues in Pondok Pesantren Daarul Ukhuwah (PPDU) Malang - Fitrianita, Titi; Ismiasih, Dwi (Islamic Insights Journal, 2020)
This study aims to explain the problems which occur in Pondok Pesantren Daarul Ukhuwah (PPDU) Malang regarding human resources management. PPDU, like anotherpesantren in Indonesia intends to obtain knowledge from both religious subjects and modern ‘secular subjects’. This program is implemented by mixing educational system in PPDU, which is essentially must be managed and regulated to produce good quality education through developing professional human resources management. However, various problems have emerged since the pesantren insists in maintaining its moral and ethical standards rather than developing professional human resources management. Using qualitative method this study shows that the poor principle and values of professional in PPDUresides in two main factors, namely the informal human resource selection and management and charismatic leadership in pesantren, affecting the learning objectives achievement in the pesantren.     Keywords : pesantren, management, problem, human resources